Activation of Frontal Neocortical Areas by Vocal Production in Marmosets - Simões, Cristiano S.; Vianney, Paulo; De Moura, Marco M.; Freire, Marco Aurelio M.; Mello, Luiz E.; Sameshima, Koichi; Araujo, John F.; Nicolelis, Miguel A.; Mello, Claudio V.; Ribeiro, Sidarta (Frontiers in Integrative Neuroscience, 2010)
Primates often rely on vocal communication to mediate social interactions. Although much is known about the acoustic structure of primate vocalizations and the social context in which they are usually uttered, our knowledge about the neocortical control of audio-vocal interactions in primates is still incipient, being mostly derived from lesion studies in squirrel monkeys and macaques. To map the neocortical areas related to vocal control in a New World primate species, the common marmoset, we employed a method previously used with success in other vertebrate species: Analysis of the expression of the immediate-early gene Egr-1 in freely behaving animals. The neocortical distribution of Egr-1 immunoreactive cells in three marmosets that were exposed to the playback of conspecific vocalizations and vocalized spontaneously (H/V group) was compared to data from three other marmosets that also heard the playback but did not vocalize (H/n group). The anterior cingulate cortex, the dorsomedial prefrontal cortex and the ventrolateral prefrontal cortex presented a higher number of Egr-1 immunoreactive cells in the H/V group than in H/n animals. Our results provide direct evidence that the ventrolateral prefrontal cortex, the region that comprises Broca's area in humans and has been associated with auditory processing of species-specific vocalizations and orofacial control in macaques, is engaged during vocal output in marmosets. Altogether, our results support the notion that the network of neocortical areas related to vocal communication in marmosets is quite similar to that of Old world primates. The vocal production role played by these areas and their importance for the evolution of speech in primates are discussed.